A prospective multicenter observational study of cell‐mediated immunity as a predictor for cytomegalovirus infection in kidney transplant recipients. Issue 9 (15th March 2019) - Kumar, Deepali; Chin‐Hong, Peter; Kayler, Liise; Wojciechowski, David; Limaye, Ajit P.; Osama Gaber, A.; Ball, Simon; Mehta, Aneesh K.; Cooper, Matthew; Blanchard, Ted; MacDougall, James; Kotton, Camille N.
Abstract : T cell immunity is essential for the control of cytomegalovirus (CMV) infection after transplantation. We evaluated a CMV‐specific peptide‐based enzyme‐linked immunosorbent spot (ELISPOT) assay to determine whether assay results could predict subsequent CMV events. Adult kidney transplant recipients at 43 centers underwent ELISPOT testing to enumerate interferon gamma (IFN‐γ) binding spot‐forming units (sfu) after stimulation of cells with an overlapping peptide pool of CMV phosphoprotein 65 (pp65) and immediate early‐1 (IE‐1) protein at the end of antiviral prophylaxis (EOP) and various time points thereafter. The primary outcome was a CMV event in the first posttransplant year. In 583 kidney transplant recipients (260 seropositive donor [D+]/seronegative recipient [R−] and 277 R+), CMV events occurred in 44 of 368 eligible patients (11.8%) at a median of 227 days (range 92‐360) posttransplant. A cutoff value of >40 sfu/2.5 × 10 5  cells for either IE‐1 or pp65 was derived as a threshold for positivity, with a negative predictive value of >97% for CMV events. CMV events were significantly lower in assay positive vs assay negative patients (3.0% vs 19.5%, P  < .0001 for pp65). Time to CMV event post‐EOP was significantly greater in those with sfu >40 at EOP ( P  < .0001). In this large, multicenter trial of kidney transplant recipients, we show that an assessment of CMV‐specific immunity using a novel ELISPOT assay is able to predict protection from CMV infection. Abstract : In a multicenter study of kidney transplant recipients, the authors show that measuring CMV‐specific T cell immunity using a novel ELISPOT assay predicts protection from CMV infection in CMV‐seropositive patients.